Software architecture patterns - Richards, Mark (O'Reilly Media, Inc., 2021)
The success of any software application or system depends on the architecture style you use. This updated report presents several common architecture styles to guide designers and developers on how to design components and to help you determine the ways in which those components should interact. Author Mark Richards takes a deep dive into many common software architecture styles. Each chapter includes a full explanation of how a particular style works, outlines its benefits and considerations, and describes the circumstances and conditions the style was designed to address. This report also presents an analysis of and scorecard for each style based on several architecture and software development quality attributes.
Keywords: Software architecture; Architecture logicielle